Micro-elimination of hepatitis C virus infection in the rural and remote areas of Taiwan – A multi-center collaborative care model - Ching-Chu Lo; Wei-Yi Lei; Ying-Che Huang; Jow-Jyh Hwang; Chen-Yu Lo; Chien-hung Lin; Hsu-sheng Cheng; Yee-Tam Liao; Po-Cheng Liang; Meng-Jau Chiou; Ming-Jong Bair; Chia-Yen Dai; et al. (Journal of Microbiology, Immunology and Infection, 2023)
Introduction: Taiwan has several hepatitis C virus (HCV) hyper-endemic areas. We aimed to evaluate the effectiveness and safety of a collaborative HCV care system with an outreach decentralized strategy among the resource-constrained rural/remote areas of Taiwan. Methods: The pilot study was conducted in four high HCV-endemic townships in the rural/remote areas of Taoyuan, Alishan, Zhuoxi and Xiulin. Registered residents who worked or lived in the four areas and were aged 30–75 years were invited to participate in this program. Multidisciplinary HCV care teams provided outreach decentralized services of anti-HCV screening, link-to-diagnosis, and link-to-treatment with direct-acting antiviral agents (DAA). The primary end-point was sustained virological response (SVR). Results: Of 8291 registered residents who were invited as the target population, 7807 (94.2%) subjects received anti-HCV screening, with the average anti-HCV prevalence rate of 14.2% (1108/7807) (range among four areas: 11.8%–16.7%). The rate of link-to-diagnosis was 94.4% (1046/1108) of anti-HCV-positive subjects (range: 90.9%–100%) with an average HCV-viremic rate of 55.1% (576/1046) (range: 50.0%–64.3%). The link-to-treat rate was 94.4% (544/576) in HCV-viremic subjects (range from 92.7% to 97.2%). Overall, 523 (96.1%) patients achieved an SVR (range: 94.7%–97.6%). Eventually, the overall effectiveness was 80.7% (range: 74.6%–93.1%). The presence of hepatocellular carcinoma at baseline was the only factor associated with DAA failure. The DAA regimens were well-tolerated. Conclusion: The outreach decentralized community-based care system with DAA therapy was highly effective and safe in the achievement of HCV micro-elimination in the resource-constrained rural and remote regions, which could help us to tackle the disparity.